Enhancement Glutathione Peroxidase Activity and α2-Macroglobulin Gene Expression of Macrobrachium rosenbergii Fed With Aqueous Morinda citrifolia Leaves Extract-Supplemented Diet - Atika Marisa Halim; Arief Prajitno; Chin Chyuan Chang (Universitas Muhammadiyah Malang, 2018)
Morinda citrifolia, known commercially as noni is often used for enhance immunity, these plant rich of phenolic compound with antioxidant properties. In the present study, Macrobrachium rosenbergii were fed with diets containing of aqueous M. citrifolia leaves extract (AMLE) at 0.6, 4 and 6 g kg-1. Glutathione peroxidase (GPx) activity was conducted to measure immune parameter, these parameter was evaluated before and after 7, 21, 35, 49 and 63 days of feeding trial. Immune gene expression of α2-macroglubulin (α2-M) was evaluated in this study. The results showed that after 63 days of feeding treatment, significantly increased in GPx activity. Gene expressions of α2-macroglubulin was significantly upregulated. These results recommend that administration of AMLE can be used as an immunostimulant and regulated immune response and immune gene expression in M. rosenbergii. Keyword: Morinda citrifolia, Macrobrachium rosenbergii, GPx, α2-M